The Influence of Digital Marketing, Market Sensing Ability, and Entrepreneurial Competence on Increasing The Income of SME in Polewali Mandar Regency, Indonesia - Chakti, Andi Gunawan Ratu; Syukur, Muhammad; Suhaeb, Firdaus W. (Golden Ratio of Data in Summary, 2025)
This study aims to analyze the influence of Digital Marketing, the ability to sense the market, and entrepreneurial competence, both individually (partially) and simultaneously, on the income increase in Micro, Small, and Medium Enterprises (SME) in Polewali Mandar Regency. This research uses a survey approach on SME in Polewali Mandar Regency from September to December 2024. The population in this study includes 31 small entrepreneurs in the Polman Regency area. The sampling technique used the Simple Random Sampling method, and the data analysis was carried out using multiple regression analysis. The study results revealed that Digital Marketing, market sensing ability, and entrepreneurial competence, both partially and simultaneously, positively and significantly influence increasing MSME sales in Polewali Mandar Regency. The research subjects include MSME owners who run marketing and sales through digital platforms like marketplaces, social media, and WhatsApp. Each MSME involved shows an increase in online sales turnover, so it can be concluded that MSME owners have good business performance in managing their business operations.